2006
DOI: 10.1021/jo061245i
|View full text |Cite
|
Sign up to set email alerts
|

Interconversion of Carbon Sites in Boat-Chair-Boat Cyclodecane; Conformations of Chlorocyclodecane and Cyclodecyl Acetate

Abstract: Interconversion of carbon sites in boat-chair-boat (BCB) cyclodecane occurs by way of the twist-boat-chair (TBC) conformation, which predicts that C-1 exchanges with C-4, etc. The previously obtained low-temperature 13C spectra could be matched by assuming (1,4) or (1,3) exchange, but not (1,2) exchange. A free-energy barrier of 5.54 kcal/mol was obtained for conversion of BCB to TBC at -137.4 degrees C. The major conformation of chlorocyclodecane and cyclodecyl acetate is assigned to the IIIe BCB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Kolossvary & Guida (1993) carried out a comprehensive study of conformational equilibration for 2with Allinger's MM2 program and concluded that (2a) equilibrates only with (2c) within a 12 kcal mol À1 window. Wiberg (2003) calculated a free-energy barrier of 5.4 kcal mol À1 for the BCB to TBC conversion at room temperature, in good agreement with a later experimental determination of this barrier (5.54 kcal mol À1 at 136 K; Pawar et al, 2006).…”
Section: Commentsupporting
confidence: 63%
See 1 more Smart Citation
“…Kolossvary & Guida (1993) carried out a comprehensive study of conformational equilibration for 2with Allinger's MM2 program and concluded that (2a) equilibrates only with (2c) within a 12 kcal mol À1 window. Wiberg (2003) calculated a free-energy barrier of 5.4 kcal mol À1 for the BCB to TBC conversion at room temperature, in good agreement with a later experimental determination of this barrier (5.54 kcal mol À1 at 136 K; Pawar et al, 2006).…”
Section: Commentsupporting
confidence: 63%
“…The low-temperature 13 C spectrum of the substituted ring carbon of chlorocyclodecane, (3), in solution showed three peaks at 67.67, 66.14 and 61.63 [(3a), (3b) and (3c), respectively], with populations of 31.2, 14.9 and 53.9% (Pawar et al, 1998). These peaks were assigned to IIe BCB, IIa BCB and a TBCC conformation, respectively, but the assignment for the major conformation, (3c), was later changed to IIIe BCB (Pawar et al, 2006). The low-temperature 13 C spectra for cyclodecyl acetate, (4), in solution show three peaks for the substituted ring C atoms, with relative positions and intensities similar to those of (3), which suggested that the populated ring conformations are the same for (3) and (4) (Pawar et al, 1998).…”
Section: Figurementioning
confidence: 99%
“…Similar calculations were also performed on cyclodecane ( 10 ). The structure of this molecule has been studied experimentally by X‐ray crystallography, gas phase electron diffraction, and NMR spectroscopy . The various conformations have been reviewed recently .…”
Section: Resultsmentioning
confidence: 98%
“…Results indicate that, in all molecular models studied, a bond path is found to exist between the congested atoms. At equilibrium, that is, for the energy minimized molecular structures, the congested atoms are found to be separated by a distance well below the sum of the van der Waals radii, an observation also confirmed by a number of available experimental structures of some of the molecules shown in Scheme and similar compounds found in the literature …”
Section: Discussionmentioning
confidence: 99%
“…The backbones ( Figure 4 d and e) of asar[9]-and asar [10]arene adopt conformations similar to those available to cyclononane and cyclodecane, respectively, while the shape of asar [10]arene is best described as a twisted chair-boat-chair (CBC) conformation. [38] Finally, the backbone (Figure 4 f) of asar [11]arene is folded up into a "taco" shape with two "grooves"-potential binding-sites for flat or rod-shaped guests.…”
Section: Resultsmentioning
confidence: 99%